2021
DOI: 10.3390/polym13244447
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich-Structured, Hydrophobic, Nanocellulose-Reinforced Polyvinyl Alcohol as an Alternative Straw Material

Abstract: An environmentally friendly, hydrophobic polyvinyl alcohol (PVA) film was developed as an alternative to commercial straws for mitigating the issue of plastic waste. Nontoxic and biodegradable cellulose nanocrystals (CNCs) and nanofibers (CNFs) were used to prepare PVA nanocomposite films by blade coating and solution casting. Double-sided solution casting of polyethylene-glycol–poly(lactic acid) (PEG–PLA) + neat PLA hydrophobic films was performed, which was followed by heat treatment at different temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Azeredo, Mattoso [ 55 ] reported that the presence and increase in the concentration of cellulose nanofibers in chitosan-glycerol films caused a significant reduction in WVP. A similar result was reported by Chou, Shi [ 56 ], who noted that the WVP of PVOH films decreased with the addition of CNC at 2.5% ( w / w ). Meanwhile, for biodegradable films made from a mixture of cassava starch, chitosan and gallic acid, the incorporation of 7.5% ( w / w ) cellulose nanofibers generated the material with the best water vapor barrier capacity [ 39 ].…”
Section: Resultssupporting
confidence: 88%
“…Azeredo, Mattoso [ 55 ] reported that the presence and increase in the concentration of cellulose nanofibers in chitosan-glycerol films caused a significant reduction in WVP. A similar result was reported by Chou, Shi [ 56 ], who noted that the WVP of PVOH films decreased with the addition of CNC at 2.5% ( w / w ). Meanwhile, for biodegradable films made from a mixture of cassava starch, chitosan and gallic acid, the incorporation of 7.5% ( w / w ) cellulose nanofibers generated the material with the best water vapor barrier capacity [ 39 ].…”
Section: Resultssupporting
confidence: 88%
“…The details on the steps and parameters of polymerization of PEG-PLA used in this study are listed in the previous article. 18 The second part was the preparation of multilayered PEG-PLA and PLA hydrophobic composites. PEG-PLA (1 wt%) and neat PLA (1 wt%) were separately dissolved in chloroform.…”
Section: Methodsmentioning
confidence: 99%
“…Three water drops (5 μL each) were tested at different selected locations on the films. Prior to testing, the films were maintained under constant conditions at three different relative humidity (RH) levels: 33%, 57%, and 75% …”
Section: Methodsmentioning
confidence: 99%
“…Prior to testing, the films were maintained under constant conditions at three different relative humidity (RH) levels: 33%, 57%, and 75%. 13 Water Solubility (WA). To measure the water resistance of the PVAbased films, a humidity chamber (RHP 80, Huanrui Test Equipment Co., Ltd.) was utilized.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation